1986
DOI: 10.1083/jcb.103.2.429
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin-plasma membrane interaction in the adhesion of hemopoietic cells.

Abstract: Many hemopoietic cell lines were examined for their ability to adhere to culture dishes coated with extracellular matrix proteins. Adhesion assay was performed with murine and human leukemic cell lines representative of different stages of differentiation along both erythroid and myeloid lineages. All the hemopoietic cell lines tested adhered to fibronectin but not to laminin, types I, III, and IV collagen, serum-spreading factor, and cartilage proteoglycans. In addition to immortalized cell lines, immature er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(31 citation statements)
references
References 43 publications
1
29
0
1
Order By: Relevance
“…In contrast, the functional requirements of the plasma membrane of the committed erythroid progenitor are vastly different. These progenitors engage in cell-cell and cell-extracellular matrix adhesion through expression of receptors for matrix components, such as the fibronectin receptors, VLA-4 and VLA-5, and a sialyated macrophage receptor (27)(28)(29)(30)(31)(32). In addition, the progenitor membrane facilitates endocytosis with, for example, transferrin receptor recycling (33-35), while the membrane of mature red cells does not undergo extensive receptor-mediated endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the functional requirements of the plasma membrane of the committed erythroid progenitor are vastly different. These progenitors engage in cell-cell and cell-extracellular matrix adhesion through expression of receptors for matrix components, such as the fibronectin receptors, VLA-4 and VLA-5, and a sialyated macrophage receptor (27)(28)(29)(30)(31)(32). In addition, the progenitor membrane facilitates endocytosis with, for example, transferrin receptor recycling (33-35), while the membrane of mature red cells does not undergo extensive receptor-mediated endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, adhesive properties have been used to distinguish hemopoietic cells with different spleen colony-forming and marrow-repopulating abilities (Bearpark and Gordon 1989). Immature myeloid and erythroid cells have been shown to bind to both fibronectin (Giancotti et al 1986) and collagen Type I (Tsai et al 1987;Koenigsmann et al 1992). Human CD34 Ï© progenitors bind to fibronectin in an activation-dependent manner (Kerst et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This was first demonstrated for erythroid cells (Patel & Lodish, 1984) and subsequently for myeloid cells (Giancotti et al 1986) and is mediated via a wellcharacterized 140K (K = 10 3 M r ) receptor on immature haematopoietic cells, which is likely to belong to the integrin family of cell adhesion molecules (Hynes, 1987). Interestingly, studies in the mouse and human have shown that adhesion of erythroleukaemia cells or erythroblasts to fibronectin is able to promote haemoglobinization, terminal differentiation and enucleation in the presence of chemical inducers or erythropoietin Tsai et al 1987).…”
Section: Importance Of Cell-cell Contact In Haematopoiesismentioning
confidence: 99%